The Interplay of Transcultural Competence, Therapeutic Communication, and Self-Efficacy Among Community Health Nurses - Dwi Nopriyanto; Bahtiar Bahtiar; Ruminem Ruminem; Rita Puspasari; Mayusef Sukmana; Iwan Samsugito; Ratna Wati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Nurses working in culturally diverse environment possess valuable knowledge and experience in fostering interpersonal communication and can strengthen their self-efficacy. Nursing competence is defined as a continuous, dynamic process of providing care to patients from diverse cultural backgrounds, aimed at reducing risk and understanding patient needs. This study aimed to investigate the relationship between transcultural nursing competence, therapeutic communication skills, and self-efficacy among community health nurses in Samarinda. A quantitative descriptive cross-sectional study was employed, involving 224 nurses from 26 public health centers in Samarinda.  Data were collected from April to June 2025 using validated questionnaires assessing transcultural nursing competence, therapeutic communication skills, and self-efficacy. Statistical analyses included chi-square tests and logistic regression to explore correlations and predictive relationships. Results showed that 52.7% of nurses demonstrated good transcultural nursing competence, 55.8% exhibited good therapeutic communication skills, and 58.5% reported high self-efficacy. Transcultural nursing competence significantly influenced therapeutic communication skills (OR=2.044, p=0.011) and self-efficacy (OR=2.256, p=0.004). Length of work also positively correlated with self-efficacy (OR=2.574, p=0.016), while demographic factors such as gender, age, and education showed no significant associations. Transcultural nursing competence emerged as a critical factor in enhancing therapeutic communication and self-efficacy among nurses. The findings highlights the importance of cultural competency training to improve nursing care in multicultural settings.Keywords: Transcultural Nursing, Therapeutic Communication, Self-Efficacy, Community Health Nurses.